Development of Interactive Learning Media Based on Articulate Storyline on Temperature, Heat, and Expansion Materials With The Wasaka Stem-K Learning Model - Prasetyo, Ambar; Annur, Syubhan; Putri, Rizky Febriyani (Berpusi Publishing, 2024)
The research on the development of articulate storyline media with the STEM-K WASAKA learning model on temperature, heat, and expansion material aims to describe the validity, practicality, and effectiveness of interactive learning media. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data collection techniques use expert validation sheets, teacher response questionnaires and student response questionnaires, and test questions. This study produced: (1) the validity score of the articulate storyline interactive learning media was 95.98% with a very valid category; (2) the practicality score of the articulate storyline interactive learning media was 95.94% by teachers and 88.33% by students, indicating very practical criteria; (3) the effectiveness score of the articulate storyline interactive learning media was obtained from the pretest and posttest values with an N-gain score of 0.7 which was categorized as very effective. Similar learning can be used and developed on other materials in science subjects and other subjects. Thus, teachers can utilize articulate storyline as an alternative interactive learning media that supports conceptual understanding and trains students' skills. Based on these results, it can be concluded that the Articulate Storyline media for temperature, heat, and expansion materials is stated to be very valid, very practical, and very effective for use in science learning for junior high school grade VII.